56.2k views
0 votes
Simplify (x-1)(x^2+5x+2)

User Nzifnab
by
5.6k points

2 Answers

5 votes

Answer:

x³ + 4x² - 3x - 2

Explanation:

Each term in the second factor is multiplied by each term in the first factor

(x - 1)(x² + 5x + 2)

= x(x² + 5x + 2) - 1(x² + 5x + 2) ← distribute both parenthesis

= x³ + 5x² + 2x - x² - 5x - 2 ← collect like terms

= x³ + 4x² - 3x - 2

User Trees
by
5.1k points
4 votes

Answer:


x^3 + 4x^2 - 3x - 2

Explanation:

You need to multiply a binomial by a trinomial.


(x-1)(x^2+5x+2) =

Multiply each term of the binomial by each term of the trinomial.


= x^3 + 5x^2 + 2x - x^2 - 5x - 2

Now, combine like terms and write answer in descending order of exponent.


= x^3 + 4x^2 - 3x - 2

User James Maroney
by
5.2k points